PENERAPAN PIDANA MATI WARGA NEGARA ASING: ANTARA KEPASTIAN HUKUM, KEPENTINGAN DIPLOMATIK DAN HAK ASASI MANUSIA - Ahmadi, Baharudin (Universitas Labuhanbatu, 2025)
This study examines the application of the death penalty to foreign citizen in Indonesia, focusing on aspects of legal certainty, diplomatic interests, and human rights. As a state governed by law, Indonesia faces the challenge of balancing the enforcement of formal rules with social norms. Although the death penalty is recognized within Indonesia's legal system, it has sparked debate regarding the violation of the universally recognized right to life. This research adopts a normative juridical approach, analyzing relevant legislation and case studies concerning the imposition of the death penalty. The findings reveal that while the death penalty provides legal certainty, its implementation must be conducted with caution to avoid injustice and abuse of power. Furthermore, the application of the death penalty to foreign citizen can impact diplomatic relations between Indonesia and the convict’s home country, as well as Indonesia's international reputation. Therefore, legal reforms are needed that consider the principles of justice, legal certainty, and utility to ensure that the application of the death penalty aligns with international standards and does not undermine the legitimacy of the law in Indonesia. This study offers recommendations for improving legal policies and practices and encourages harmonization with international human rights standards.Keywords: Diplomacyt; Human Rights; Death Penalty; Foreign Citizen